2014
DOI: 10.1016/j.jbi.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

ReVeaLD: A user-driven domain-specific interactive search platform for biomedical research

Abstract: Bioinformatics research relies heavily on the ability to discover and correlate data from various sources. The specialization of life sciences over the past decade, coupled with an increasing number of biomedical datasets available through standardized interfaces, has created opportunities towards new methods in biomedical discovery. Despite the popularity of semantic web technologies in tackling the integrative bioinformatics challenge, there are many obstacles towards its usage by non-technical research audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 34 publications
0
35
0
4
Order By: Relevance
“…The user can also select relevant filters (numerical and textual) through the 'Topic-based' builder. Our implementation exposes a REST API and provides a visual query system, named ReVeaLD [12], for intuitive query formulation and domain-specific uses [10]. The catalogued subclasses of few Qe and as a result the total number of distinct instances retrieved per Qe while querying using DSQE is shown in Fig.…”
Section: Domain-specific Query Enginementioning
confidence: 99%
See 1 more Smart Citation
“…The user can also select relevant filters (numerical and textual) through the 'Topic-based' builder. Our implementation exposes a REST API and provides a visual query system, named ReVeaLD [12], for intuitive query formulation and domain-specific uses [10]. The catalogued subclasses of few Qe and as a result the total number of distinct instances retrieved per Qe while querying using DSQE is shown in Fig.…”
Section: Domain-specific Query Enginementioning
confidence: 99%
“…3). The linked concepts and literals are displayed as nodes arranged in a force-directed concept map representation, as previously introduced in [12]. The Qe used for linking are displayed as Light Brown-colored nodes, whereas catalogued concepts (Blue-colored nodes) are linked to these Qe using the voidext:subClassOf.…”
Section: Visualization Of the Mapped Lslod Cloudmentioning
confidence: 99%
“…The KPC also provides a Visual Query System -ReVeaLD 13 (Real-time Visual Explorer and Aggregator of Linked Data) for facilitating non-technical biomedical users to intuitively formulate advanced SPARQL queries by interacting with a visual concept map representation of CanCO [18]. Results are aggregated from the LBDS and presented in a data browser with 'Smart Icons', which render domain-specific visualizations using a set of Qe-based Graphic Rules, and refer to additional information available on portals like ChemSpider [25] and PubChem [21].…”
Section: Knowledge Publishing Componentmentioning
confidence: 99%
“…SPARQL endpoints under the Bio2RDF Release 2 were integrated later in May 2013 due to better uptime. To aid the non-technical users we created a screencast 17 outlining the different steps (Workflow II, III), which was made available on the project website and has been downloaded by ∼175 users 18 by October 2013. Google Analytics tracking showed that ReVeaLD was accessed by 387 distinct users from 29 countries, up to February 2014 (Fig.…”
Section: Evolution and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation